Educational Assessment Reassessed - Sanders, William L.; Horn, Sandra P. (Education Policy Analysis Archives, 1995)
For decades, the assessment of educational entities–school systems, individual schools, and teachers–has evoked strong and sometimes violent emotions from the educational community, the general public, and their legislative representatives. In spite of attempts to codify standards for the evaluation of these entities, assessment experts remain denominationalized–often religiously so. Methods of assessment based on the use of standardized tests have come under intense fire in recent years with some critics going so far as to call for their complete elimination. Those who advocate alternative methods of assessment have become increasingly outspoken in establishing exclusive rights to the legitimate assessment paradigm. However, some of the most respected advocates of alternative assessment have taken a more moderate view, warning against an "either-or" mentality (Brandt, 1992, p. 35). Reflecting this more moderate perspective, this paper strongly advocates the use of multiple indicators of student learning, including those provided by standardized tests.